Levothyroxine/Liothyronine Combination Therapy and Quality of Life: Is It All about Weight Loss?. Issue 5 (13th October 2018) - Michaelsson, Luba Freja; la Cour, Jeppe Lerche; Medici, Bjarke Borregaard; Watt, Torquil; Faber, Jens; Nygaard, Birte
Abstract : Objectives: According to one hypothesis, the popularity of levothyroxine (L-T4 )/liothyronine (L-T3 ) combination therapy relates to weight loss. The purpose of this study was to detect a possible correlation between thyroid-related quality of life (QoL) and weight loss in hypothyroid patients switched from L-T4 monotherapy to L-T4 /L-T3 combination therapy. Methods: In an open-label cohort study, all hypothyroid patients referred to the University Hospital endocrine clinic due to persistent symptoms despite adequate L-T4 monotherapy (without other explanations for the symptoms) were switched from L-T4 monotherapy to L-T4 / L-T3 combination therapy at a ratio of approximately 17/1. At baseline and after 3 months of treatment we measured: QoL by the Thyroid Patient-Reported Outcome (ThyPRO-39) questionnaire, thyroid hormones, body weight, body composition by a DEXA-scan, and cognitive function by evaluating participants' reaction time as well as working memory by the California Computerized Assessment Package (CalCAP®). QoL was re-evaluated after 12 months. Results: Twenty-three patients participated (91% women, median age 47 years). The ThyPRO-39 composite score decreased from a median of 54 (quartiles: 34, 74) to 15 (11, 28) after 3 months ( p < 0.0001), and 20 (14, 26) after 12 months, indicating a better QoL. There was no change in body weight, and no correlations between QoL and weight. There was a slight improvement in cognitive function, whereas body composition, heart rate, and serum TSH did not change. Conclusion: Our study on hypothyroid patients switched from L-T4 monotherapy to L-T4 /L-T3 combination therapy showed a substantial improvement in QoL measured by the ThyPRO-39. This improvement could not be explained by weight loss.